Radiation hardness of indium oxide films in the Cooper-pair insulator state - Lazarević Đorđe R.; Vujisić Miloš L.; Stanković Koviljka Đ.; Dolićanin Edin Ć.; Osmokrović Predrag V. (Nuclear Technology and Radiation Protection, 2012)
This paper investigates possible radiation effects in the Cooper-pair insulator state of indium oxide films. Radiation effects are predicted on the basis of Monte Carlo simulations. Results of a combined theoretical and numerical analysis suggest that radiation-induced changes in the investigated films could significantly affect their current-voltage characteristics, and that a transition to a metallic state is possible, due to radiation-induced disruption of the fine-tuned granular structure. Dissociation of Cooper pairs, caused by both the incident radiation and the ions displaced within InOx films, can also destroy the conditions for this specific insulating state to subsist.